Some Strange - Anachronic Attitudes of Mr. Zoran Janjetović on Emigration of the Muslim Population of Yugoslavia in Turkey - Salim Kadri Kerimi (Historijski pogledi, 2024)
In the Journal of the Institute for Recent History of Serbia, Belgrade – “Tokovi istorije”, 3/2022, among other articles, an “Original scientific paper” was published, in English, by dr. Zoran Janjetović, a scientific advisor in the mentioned Institute, on the Emigration of the Kosovo Albanians into Turkey during the 1950s of the 20th century. In the same article, the author rightly partially referred to the question of the emigration of the rest of the Muslim population of Yugoslavia to Turkey, before and after the Second World War. After reading and analysing the such article, I came to the conclusion that the mentioned paper is certainly original, but, in my opinion, by no means scientific. In other words, in the time when almost all archival material is available for the research of the mentioned problem, to conclude that the emigration of Albanians, Turks, Boshniaks and other Muslims of Kosovo and the FPR of Yugoslavia as a whole, in Turkey, after the Second World War, was free/ according to their free will, in my opinion and deep conviction, is beyond all logic and historical truth. For example, the conclusions of Mr. Zoran Janjetović: a) „…partial emigration of ethnic Turks was acceptable, but the emigration of all Muslims, especially Albanians, was considered politically harmful. To prevent this, the Macedonian territory was divided into 'blocks' based on the number of ethnic Turks. Emigration was permitted from areas with a larger number of Turks, but not from those with a smaller number“; b) „The Yugoslav and Serbian authorities opposed the emigration of non-Turks from the very beginning, and this policy remained in place for a long time, especially for Muslims outside of Macedonia. Claims by some Western authors that the 'Serbian' authorities allegedly wanted to expel Albanians are unfounded. On the contrary, until 1957, the authorities in Serbia were against emigration from Kosovo, and the Federal government also wanted to limit emigration only to Macedonian Turks “; and, c) „The Muslims started to emigrate to Turkey after a ‘gentlemen’s agreement’ of 1953 between Tito and Turkish Foreign Minister Fuat Köprülü. The agreement foresaw emigration of ethnic Turks from Macedonia, but other Muslims tended to join them. Because of that the Yugoslav authorities strove to limit emigration only to Turkish - inhabited parts of Macedonia. This failed because Muslims came to Macedonia from other parts of the country in order to emigrate. Among these emigrants there was a certain number of Kosovo Albanians. Like the Turks, they emigrated for religious, economic and social reasons… The article shows that the Yugoslav authorities in no way supported Albanian emigration, but rather that they tried to stop it“, in my opinion, are untrue and scientifically unfounded. In other words, according to my knowledge, and as cited in my book and in several of my articles on this subject, the mass emigration of the Muslim population, including the emigration of the Albanians from Yugoslavia to Turkey, after the Second World War started аs a result of the flagrant abuse of the mentioned bilateral agreement, by the Yugoslav/ Macedonian authorities. The emigration to Turkey was allowed not only to a small portion of Turks, as previously was agreed upon, but rather to the Turkish and the rest of the Muslim population as a whole. That the stated conclusions of Mr. Z. Janjetović are not correct, among other things, is confirmed by the final result of the mass emigration not only the Turks, but also a large number of Albanians and other Muslim populations.